2002
DOI: 10.1002/gcc.10112
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory subunit type I‐α of protein kinase A (PRKAR1A): A tumor‐suppressor gene for sporadic thyroid cancer

Abstract: The tumor-suppressor gene encoding the cyclic AMP-dependent protein kinase A type I-alpha regulatory subunit PRKAR1A has been mapped to chromosome 17 (17q22-24) and is mutated in Carney complex, a familial neoplasia syndrome that is associated with thyroid tumors. Other genes implicated in cyclic nucleotide-dependent signaling have been investigated in thyroid tumorigenesis. We studied protein kinase A (PKA) activity in noninherited follicular thyroid adenomas and follicular, papillary, and undifferentiated (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 59 publications
4
68
0
Order By: Relevance
“…Of the down-regulated genes, DUSP 1, which has known proliferation and differentiation functions, has been shown previously to be down-regulated in follicular carcinomas (17) and in advanced epithelial ovarian cancer (30). We also noted the PKIA gene, a potent inhibitor of protein kinase B, to be down-regulated in follicular carcinomas compared with adenomas, supporting previous molecular studies of sporadic thyroid cancer (31). As in earlier studies, the VEGF gene was characteristically noted in follicular carcinomas (32,33).…”
Section: Discussionsupporting
confidence: 88%
“…Of the down-regulated genes, DUSP 1, which has known proliferation and differentiation functions, has been shown previously to be down-regulated in follicular carcinomas (17) and in advanced epithelial ovarian cancer (30). We also noted the PKIA gene, a potent inhibitor of protein kinase B, to be down-regulated in follicular carcinomas compared with adenomas, supporting previous molecular studies of sporadic thyroid cancer (31). As in earlier studies, the VEGF gene was characteristically noted in follicular carcinomas (32,33).…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the presence of PRKA1A mutations in adrenocortical adenomas and their absence in adrenocortical cancers (16), but it is the opposite of what is observed in thyroid tumors in which PRKA1A mutations are associated with the malignant phenotype (17). This suggests that with regard to the role of PKA, diverse tumorigenic processes exist in endocrine cells of different origin.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, we showed that two potential target proteins, R1␣ subunit of PKA and CD52 antigen, were highly expressed in the ATRA-treated APL cells. Recently, Sandrini et al 52 reported that PKA-R1␣ acted as a tumor-suppressor gene for sporadic thyroid cancer. The administration of ATRA has been used to treat patients with APL, but ATRA alone is not necessarily sufficient to maintain patients in stable remission.…”
Section: Resultsmentioning
confidence: 99%